Student’s Mathematical Reasoning Ability Viewed from Self-Confidence in Mathematical Modeling with Open-ended Approach Learning - Susanti, Desmiani; Budi Waluya, St.; Rosyida, Isnaini (Unnes Journal of Mathematics Education Research, 2020)
The objectives of this study are (1) to examine the quality of learning with Open-ended Mathematical Modeling towards mathematical reasoning ability; (2) describe the achievement of mathematical reasoning abilities in terms of self-confidence. The research method used is a mix method with concurrent embedded design. The research subjects were students of 1st Public High School in Payung class Science of 11th grade. The quantitative research is true experimental research with Pretest-Posttest Control Group design. Quantitative data were tested with the z test, while qualitative data were analyzed descriptively. The results showed that (1) learning with Mathematical Modeling with Open-ended approach gave good quality; (2) students with low self-confidence can estimate the allegations and check the truth of the statement well but cannot draw conclusions logically, students with self-confidence are able to check the truth of the statement, provide an explanation of the picture and estimate the allegation but still make a little mistake in drawing conclusions logically, students with high self-confidence can check the truth, draw conclusions, estimate allegations very well, but make a few mistakes in giving explanations from images, the indicators of giving explanations from images are the most difficult indicators to be achieved by students in all categories of self-confidence.